The Effect of Money Ethics Toward Tax Evasion with Gender and Materilalistic as A Moderating Variable - Oktaviani, Rachmawati Meita; Yulinar, Anita (Jurnal Dinamika Akuntansi, 2018)
Tax is one of the important elements in the revenue budget in Indonesia. Revenue from this sector is always strived to meet the target revenue. In some times the amount of tax receipt is always not in accordance with the targets set. Tax evasion efforts made by the taxpayer is important to get the attention of the state. This study aims to conduct testing and analysis of tax evasion efforts made by the taxpayer. Tests and analysis is done by using variable approach of money ethics, gender and materiality to tax evasion.Populasi in this research is taxpayer SME registered in Tax Office Primary Kudus. Sampling technique used with convinience sampling method. The number of samples used in the study were 118 respondent. Data collection is done by dividing the questionnaire on the respondent. While the data analysis technique used is the regression analysis by using the absolute differences. The results of this study are as follows: 1), money ethics has significant effect on tax evasion; 2), gender variables as moderators proved to strengthen the positive relation of money ethics to tax evasion; 3) while the materiality variable does not moderate the significant positional relationship of money ethics to tax evasion